THE ROLE OF AMAZEMENT ON SPIRITUAL TOURISM OF THE KE'TE KESU ANCESTRAL CEMETERY - Nur Pratiwi; Achmad Sudiro; Fatchurrohman Fatchurrohman; Ananda Sabil Hussain (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2022)
This study aims to examine the structural model that integrates the variables of experience quality, amazemet and behavioral intention. The variable of amazement is the development of the concept of positive emotions, and the context of spiritual tourism is a research context that has not been studied much. This research was conducted in the ancient cemetery of the ancestors of the Toraja Ke'te Kesu tribe. 300 questionnaires were collected in this study and processed using the PLS technique with the help of smart PLS. The results of this study indicate that the Quality of experience and Amazement are antecedents of behavioral intentions, and amazement plays a role in partially mediating the relationship between experience quality and behavioral intentions.